STUDY ON ACUTE ADVERSE DRUG REACTIONS OF ANTISNAKE VENOM IN A RURAL TERTIARY CARE HOSPITAL - Deshmukh, Vinod S; Motghare, Vijay M; Gajbhiye, Dharmendra; Sv, Birajdar; Deshpande, Rushikesh; Pise, Harshal; Jaykare, Swapnil (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Snake bite is a major occupational hazard especially in rural areas. Majority of the anti-venom reactions are wrongly attributed to envenomation. There is inadequate reporting of anti-venom reactions leading to the paucity of true data of morbidity and mortality. The aim was to evaluate the adverse drug reaction (ADR) profile of anti-snake venom serum (ASV) in a rural tertiary care hospital. Methods: A prospective, observational study was conducted. A total number of 50 indoor cases of snake bites from May 2012 to January 2013 was included in the study, and the anti-venom reactions were assessed. In addition, basic epidemiological data and prescribing practices of ASV were also analyzed. Results: The incidence of snake bite was more in males (64%) as compared to females (36%) attributed to their out dwelling lifestyle. Vasculotoxic snake bites were more common (46%) than neuroparalytic ones (44%). Mild envenomation was the most common presentation. A total of 31 (62%) patients who received ASV suffered from anti-venom reactions. The most common nature of the reaction was chills, rigors (23.53%) followed by hypotension (21.57%). 52.94% cases of adverse reactions were of early anaphylactic type followed by 45.1% cases of pyrogenic reactions. 43.14% of cases of anti-venom reactions were probable in nature, and 13.73% were certain in nature with World Health Organization-Uppsala Monitoring Centre classification of ADRs. By using modified Hartwig Seigel scale, 70.59% cases were mild in severity, and 5.88% were severe in nature. Most of the reactions were classified as not preventable with the Schumock Thornton criteria. All the reactions were classified as hypersensitivity reactions with Karch and Lasanga classification. Conclusions: Present study showed a higher incidence of reactions to ASV at our institute. There was an inadequate documentation of clinical findings, investigations, and adverse reactions in most of the case papers. Keywords: Anti-snake venom, Adverse drug reactions, Pharmacovigilance, Snake bite.